(untitled) (Research, Society and Development, 2021)
The commercial value of passion fruit has great relevance; however, the agronomic potential of wild species has not been fully explored. The objective was to discuss about passion fruit and its potentials from an economic perspective. The research has a qualitative approach, of an exploratory nature, whose procedures are characterized as narrative review. The research was carried out in the year 2021 from documents indexed in journals in the area from selected descriptors. Inclusion and exclusion criteria were considered, resulting in five documents for analysis. From the bibliographic search carried out it was possible to determine that there are promising potentials, especially in the market, for passion fruit-do-mato. Due to its resistance to drought, handling, and different types of soil, its different forms of processing, and its phytotherapeutic potential, for example, the species composes a list of perspectives that culminate in quality products. In this perspective, more studies are needed that can bring reflections that make the debate broader and more efficient, as well as practical data that allow the discovery of these potentialities.